Media Kontrol Ibadah Siswa Sekolah Dasar Islam Terpadu Attaqwa Kota Bekasi Via Daring Dengan Buku Mutaba’ah - Ade Nailul Huda; Abdul Mutakabbir (At-Ta'lim : Media Informasi Pendidikan Islam, 2023)
Abstract: Media Control of Worship of Attaqwa Integrated Islamic Elementary School Students in Bekasi City Via Online with Mutaba'ah BooksOnline learning during Covid-19 has its own challenges, especially parents who are teachers at home. Therefore, control is needed for students. One of them is the Mutaba'ah book as a guidebook for monitoring student worship during online learning. This study aims to determine the media used by Elementery School Islamic IntegratedAttaqwa to monitor students' worship activities during online learning by using Mutaba’ah books. The approach used is a case study with a qualitative method. They collected data by interviews with six parents of students from grades 4, 5, and 6. As for the technique, the data analysis is as follows, data collection, data reduction, data presentation, and concluding.The results showed a decrease in the worship activities of Elementery School Islamic IntegratedAttaqwa students during online learning during the COVID-19 pandemic. The solution is Elementery School Islamic IntegratedAttaqwa used Mutaba’ah books that were used by teachers and parents to supervise students' worship activities. This study contributes to proving the benefits of the Mutaba’ah book to monitor students' worship activities during online learning.Abstract: Media Kontrol Ibadah Siswa Sekolah Dasar Islam Terpadu Attaqwa Kota Bekasi Via Daring Dengan Buku Mutaba’ahPembelajaran daring selama Covid-19 memiliki tantangan tersendiri, khususnya orang tua yang menjadi guru pendamping di rumah. Oleh karena itu, diperlukan kntrol kepada siswa. Salah satunya dengan buku Mutaba’ah sebagai buku pedoman untuk memantau ibadah siswa selama pembelajaran daring. Penelitian ini bertujuan untuk mengetahui media yang digunakan SDIT Attaqwa untuk memantau kegiatan ibadah siswa selama pembelajaran daring dengan menggunakan buku Mutaba’ah  . Pendekatan yang digunakan adalah studi kasus dengan metode kualitatif. Pengumpukan data dilakukan dengan cara wawancara terhadap enam orang tua siswa kelas 4, 5, dan 6. Adapun teknik analisis datanya adalah sebagai berikut, pengumpulan data, reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan adanya penurunan aktivitas ibadah siswa SDIT Attaqwa selama pembelajaran daring di masa pandemi COVID-19. Solusinya adalah SDIT Attaqwa menggunakan kitab Mutaba’ah yang digunakan guru dan orang tua untuk mengawasi kegiatan ibadah siswa. Kajian ini berkontribusi untuk membuktikan manfaat kitab Mutaba’ah untuk memantau aktivitas ibadah siswa selama pembelajaran daring.